Do not intubate!? Management of acute respiratory failure in the elderly Do not intubate!? Management der akuten respiratorischen Insuffizienz bei alten Patienten - Christ, M.; Esch, E.; Singler, Katrin; Heppner, Hans Jürgen (Atemwegs- und Lungenkrankheiten, 2016)
Demographic shift leads to an increasing number of elderly critically ill patients with various comorbidities and functional limitations. This very specific group is on high risk for complications and worse outcome. Non-invasive ventilation (NIV) early applied is a suitable alternative to endotracheal intubation. Ventilator associated pneumonia is less, patient communication is possible as well as intermitted ventilation. Therefore basic knowledge in geriatrics is necessary and physiological special characteristics in the elderly should be known. ICU staff has to be well-trained in using NIV. Also the equipment should be adapted to the needs of elderly critically ill patients and successful treatment is always an interdisciplinary approach in these special cases.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Geriatric; Intensive care; NIV; Non-invasve ventilation; Respiratory insufficiency